pH-Sensitive Strips Based on Cellulose and Anthocyanins from Dried Java Plum Fruits (Syzygium cumini) - Wathon, Muhammad Hizbul; Susilowati, Endang; Ariani, Sri Retno Dwi (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2023)
This study aimed to develop pH-sensitive strips made of cellulose incorporated with anthocyanins extracted from dried Java plum fruits (Syzygium cumini) which potentially can be used to monitor food freshness. The spoilage of animal protein typically produces total volatile basic nitrogen (TVB-N), which can be easily detected using pH-sensitive indicators. pH-sensitive indicators can be developed by combining biopolymers and anthocyanins. Biopolymers were cellulose from Whatman filter paper. While anthocyanins in this study were extracted from dried Java plum fruits (Syzygium cumini) with acidified water (0.01% v/v HCl) followed by SPE. Anthocyanins were incorporated into Whatman filter paper and dried at 70 °C for 10 min. Cellulose incorporated with anthocyanins was analysed using FT-IR and tested for pH 7-10. LC-MS spectra showed cyanidin-3-O-glucoside (m/z 449.3), delphinidin-3-O-glucoside (m/z 465.3), and petunidin-3-O-glucoside (m/z 479.3). These anthocyanins were the products of the deglycosylation of anthocyanin diglycosides. The deglycosylation of anthocyanins takes place through two different routes in either hemiketal or quinonoid forms. Those proposed two pathways are through protonation on an oxygen atom connecting an aglycone and a sugar moiety or through protonation on an oxygen atom within a sugar ring moiety. UV-Vis studies showed the colour profiles of anthocyanins in buffer solutions pH 1-12. The λvis-max of flavylium at pH < 3 ranged from 515-524 nm. At pH 4 to 6, colourless hemiketal was observed. The λvis-max of the quinonoid base was 575 nm at pH 7 and 590-599 nm for quinonoid anion at pH > 8. In alkaline pH, chalcone was observed.